ANALISIS DIMENSI DAN KULITAS PELAYANAN PUBLIK PEMERINTAH KECAMATAN WOLO KABUPATEN KOLAKA - Muhammad Basri; Firdaus Anas (Journal Publicuho, 2022)
This study examines the quality and accountability of public services in the Wolo District. The data collection method was carried out using a questionnaire circulated through a google form link to 109 respondents from 14 villages and villages in the Wolo District with characteristics between the ages of 15-65 years. Use SPSS (statistical package for the social sciences) version 20 tool to analyze data descriptively. The research results showed that the quality of public servants, especially sensitivity to the aspirations of the community, and the openness of the apparatus to the community are excellent. The value of efficiency and effectiveness of services is carried out properly, which is supported by the supervision of the leadership. There are service standards (SOPs) as guidelines. The personal behavior and attention of the apparatus to the community are excellent. However, some consider that the speed of responding to people's complaints is still low because professionalism and expertise are still low.